Implementasi Turbin Listrik Mikrohidro sebagai Sumber Energi Listrik untuk Perkebunan Rakyat di Desa Gurah, Aceh Besar - Suriadi, Suriadi; Fathurrahman, Fathurrahman; Akram, Akram; Amir Azan, Said; Al Huda, Nafisah (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2023)
The implementation of community service is one of the important tasks of tertiary institutions which requires educators to implement ideas that can directly benefit the community. This activity was carried out in accordance with the theme "Product-based Community Service" which aims to utilize renewable energy in the form of electrical energy and increase community economic resilience through the development of hydroelectric turbines with screw designs. To meet the need for electrical energy which is important for human life, alternative and efficient sources of electricity are needed. One alternative energy source that can be used is the Micro Hydro Power Plant (PLTMH). In this service, we have succeeded in developing a hydroelectric power plant that uses a screw turbine. The existence of this power plant has the potential to educate the community in the Gurah village plantation about power generation technology based on the energy sources around it. The main objective of this service is to produce a PLTMH with a capacity of 500 W which uses an electric generator run by a low-speed screw turbine. The results of this service activity have succeeded in providing electricity for street lighting in the Gurah plantation area, and it was successfully completed according to the planned target and time. This community service activity aims to overcome the energy crisis experienced by the Gurah village plantation community by introducing PLTMH technology that can work optimally based on existing natural potential. One of the main problems faced by partners is the installation of lighting, and through the development of PLTMH using screw turbines, we have managed to overcome this problem properly.